2021
DOI: 10.1029/2020gl091559
|View full text |Cite
|
Sign up to set email alerts
|

Global Distribution of Reversed Energy Spectra of Ring Current Protons Based on Van Allen Probes Observations

Abstract: Energy spectra of ring current protons are crucial to understanding the ring current dynamics. Based on high‐quality Van Allen Probes RBSPICE measurements, we investigate the global distribution of the reversed proton energy spectra using the 2013–2019 RBSPICE data sets. The reversed proton energy spectra are characterized by the distinct flux minima around 50–100 keV and flux maxima around 200–400 keV. Our results show that the reversed proton energy spectrum is prevalent inside the plasmasphere, with the occ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 51 publications
(74 reference statements)
2
1
0
Order By: Relevance
“…Our results showed that the H + ion fluxes increased with increasing energies, consistent with the results reported by Yi et al. (2021), where they showed a global distribution of the proton energy spectra over 2013–2019 RBSPICE data set. They found that peculiar flux minima at low energy (50–100 keV) and flux maxima at higher energies (200–400 keV).…”
Section: Discussion and Summarysupporting
confidence: 93%
See 1 more Smart Citation
“…Our results showed that the H + ion fluxes increased with increasing energies, consistent with the results reported by Yi et al. (2021), where they showed a global distribution of the proton energy spectra over 2013–2019 RBSPICE data set. They found that peculiar flux minima at low energy (50–100 keV) and flux maxima at higher energies (200–400 keV).…”
Section: Discussion and Summarysupporting
confidence: 93%
“…Our results show that the dynamics of the proton fluxes is highly energy dependent. This is consistent with the studies by Gkioulidou et al (2015) and Yi et al (2021). Gkioulidou et al (2016) studied the H + ion pressure evolution using Van Allen Probes data and found that the convection process is mainly responsible or the transport and acceleration of <80 keV H + ion, while the radial diffusion is more dominant for (>100 keV) H + ion.…”
Section: Discussion and Summarysupporting
confidence: 89%
“…The plasmasphere, which is full of cold and dense plasma (electrons ∼1 eV with density ∼10 2 –10 4 cm −3 ), plays an important role in modulating the fluxes of energetic particles in the Earth's ring current and radiation belts (e.g., Cao et al., 2017; Darrouzet et al., 2009; Fu et al., 2020; Gu et al., 2011, 2012, 2020; Hua et al., 2019; Kozyra et al., 1995; Lemaire & Gringauz, 1998; Ni et al., 2013; Orr & Webb, 1975; Sandel et al., 2003; Takahashi & Anderson, 1992; Webb & Orr, 1975; Yi et al., 2021; Zhou et al., 2020). The plasmasphere strongly influences the plasma properties of the inner magnetosphere by wave‐particle interactions (e.g., Fu et al., 2016; Gary et al., 1994; Hua et al., 2020a; Ni et al., 2017, 2014; Thorne & Horne, 1992; Wilson et al., 1992; Xiang et al., 2018; Young et al., 1981), and contributes to assessing the low‐latitude boundary layer and plasma sheet (e.g., Cao et al., 2016; Elphic et al., 1997).…”
Section: Introductionmentioning
confidence: 99%